USING “TANGRAM SULTANâ€ (FOLKSTORY GAMES) FOR INTRODUCING ANGLES AND SIDES AT ELEMENTARY SCHOOL - Yenita Roza; Syarifah Nur Siregar; Tut Wuri Handayani; Tuti Alawiyah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
Many students struggle to recognize sides and angles, especially when shapes are irregular. Since playing is a natural activity for children, it can be used as an effective learning strategy. This study aims to develop a game-based learning media to help elementary school students learn geometry. The media developed is called Tangram Sultan, a geometry game combined with folklore from the Siak Sultanate in Riau. This study presents the development of Tangram Sultan using the ADDIE development model. The Tangram Sultan game was tested at SD IT Alfityah Pekanbaru Riau. The Tangram Sultan game is used as a medium to develop students' understanding of the angles and sides of various shapes of two-dimensional figures with the following activity stages: (1) introduction of Tangram Sultan media, (2) use of media according to learning objectives, and (3) evaluation of learning process. These media have been successful in helping students to identify angles and sides and count the number of sides and angles found in various unusual two-dimentional figures. Results showed that the media successfully helped students identify and count sides and angles in irregular shapes. 66% of students correctly identified the number of sides, and 69% correctly identified the number of angles. The game also made the classroom environment more fun and engaging. This study opens up possibilities for teachers to use a combination of different games in local contexts.